Synthesis of Di-(N-tropinonyl)pyridines and Di-(N-tropinonyl)benzenes - Choi1, S.K.; Song1, J.H.; Lee1, E.J.; Jung1, S.K.; Jang1, K.Y.; Kim1, Y.Y.; Jung1, D.I.; Hahn2, J.T. (Asian Journal of Chemistry, 2011)
As a part of a research program related to the synthetic study of pharmacologically interesting tropane compounds, we synthesized di-(Ntropinonyl) pyridines 7, 8, 9 and di-(N-tropinonyl)benzenes 12, 14. p-Dipyrrolylbenzene 10, 8-(4-pyrrol-1-yl-phenyl)-8- azabicyclo[3.2.1]octan-3-one 11 and 8-(3-pyrrol-1-yl-phenyl)-8-azabicyclo[3.2.1]-octan-3-one 13 as byproducts were synthesized. However, the reaction of 1,2-phenylene diamine with 2,5-dimethoxy tetrahydrofuran, acetone dicarboxylic acid and conc. HCl in water did not give 1,2-di-(8-azabicyclo[3.2.1]octan-3-onyl)benzene 15. We suppose that the major reason is the steric hindrance of tropane rings.